2009
DOI: 10.1038/onc.2009.187
|View full text |Cite
|
Sign up to set email alerts
|

Cancer targeted gene therapy of BikDD inhibits orthotopic lung cancer growth and improves long-term survival

Abstract: Lung cancer is a leading cause of cancer death due to the high incidence of metastasis; therefore novel and effective treatments are urgently needed. A current strategy is cancer specific targeted gene therapy. While many identified cancer specific promoters are highly specific, they tend to have low activity compared to the ubiquitous CMV promoter, limiting their application. We developed a targeted gene therapy expression system for lung cancer that is highly specific with strong activity. Our expression vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Unlike eAFP-VISA-Luc, mice treated with CMV-Luc showed strong signals in the thoracic area (lungs and heart) (Figures 2a and 3a). These findings suggest that after systemic delivery, the CMV-Luc:liposome complexes flowed through the circulatory system, remained mostly in the lungs and heart, and expressed luciferase because of non-specificity of the CMV promoter, and this data is consistent with the previous studies (Xie et al, 2007Sher et al, 2009).…”
Section: Afp Promoter Is Selectively Activated In Liver Cancer Cellssupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike eAFP-VISA-Luc, mice treated with CMV-Luc showed strong signals in the thoracic area (lungs and heart) (Figures 2a and 3a). These findings suggest that after systemic delivery, the CMV-Luc:liposome complexes flowed through the circulatory system, remained mostly in the lungs and heart, and expressed luciferase because of non-specificity of the CMV promoter, and this data is consistent with the previous studies (Xie et al, 2007Sher et al, 2009).…”
Section: Afp Promoter Is Selectively Activated In Liver Cancer Cellssupporting
confidence: 91%
“…At the time of initial design, the versatility of the expression system was also taken into consideration so that it can be used in various cancer types by replacing promoter and therapeutic gene accordingly. Thus far, in addition to the pancreatic model mentioned above (Xie et al, 2007), we have also demonstrated success in tumor reduction in both lung (Sher et al, 2009) and ovarian ) cancer preclinical models.…”
Section: Introductionmentioning
confidence: 86%
“…All the plasmids used in this study were constructed as previously described (5). To test promoter activity, we used dual-luciferase reporter assay (Promega) to normalize transfection efficiency according to the manufacturer's instructions.…”
Section: Evaluation Of Promoter Activity and Cytotoxicitymentioning
confidence: 99%
“…Previously, we showed that a lung cancer-specific promoter, survivin, is highly active in lung cancer cells but not in other cell types, including immortalized normal cell lines (5). Briefly, survivin is a member of the inhibitor of apoptosis gene family that mediates several antiapoptotic functions (6,7), and its expression is associated with disease progression and poor prognosis in many cancer types (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation